If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1n + 2n = 4 Combine like terms: -1n + 2n = 1n 1n = 4 Solving 1n = 4 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Divide each side by '1'. n = 4 Simplifying n = 4
| -8b=-117 | | -7x-3=4 | | 6n-7=2n+17 | | 11x-4x^2-344= | | 1/3(s-2)=s+4 | | (x+9)(x+9)=18 | | 344=11x-4x^2 | | 3(2z-1)=6z+5 | | -28=-7(1-8b)-5(4b-3) | | (x-2)(x+3)=24 | | 32x+1=3+6 | | 2x+1+6x=81 | | -6n+9=1-8n | | -17b=-2.21 | | -17=-2.21 | | 7x-3=2x-12 | | y=-4+3x | | -34e=-3.74 | | 5x+1-7=-1 | | 25+37-2x=11 | | y=-3x+(-4) | | 8y+8=21 | | 5(9p+6)=8p | | 4x^2-6x=3 | | y=abs(x) | | 3x+2(x+2)=13-(x+2) | | -42-21= | | w-2=-4+7 | | 4x^4-5x^2-9=0 | | 4x-1+2x+15=8x+8 | | x+2x-6=6 | | 3a+2b=90 |